Making a case for just agricultural transformation in the UNFCCC: An analysis of justice in the Koronivia Joint Work on Agriculture - Sarku, Rebecca; Tauzie, Mapenzie; Whitfield, Stephen (Frontiers in Sustainable Food Systems, 2023)
The Koronivia Joint Working Group on Agriculture (KJWA) is a key forum for debating global agricultural change and integrating agricultural transformation priorities into the mechanisms of the United Nations Framework Convention on Climate Change (UNFCCC). As such, it provides an opportunity to further the (as yet underdeveloped) discourse around social transformation and just transformation in agriculture. At the conclusion of this four year process, we ask: to what extent and in what ways has a just agricultural transformation been envisioned within the Koronivia Joint Working Group on Agriculture? The paper presents a review of written submissions, workshops and concluding statements from across the full programme of KJWA workshops, meetings and consultations. We find that references to just transformations in agriculture, within KJWA are largely implicit, but not absent. We argue that justice has been most obvious and evident when it comes to discussion about who is (and where are) the most vulnerable to climate change and variability, and how access to climate smart technologies and information is distributed. Less evident have been discussion about just representation in the governance and visioning of agricultural transformation, and there have been few explicit appeals to address the historical injustices that have shaped agricultural and rural livelihoods in the Global South. We argue that following its conclusion, there is a danger that the outcomes of KJWA become reduced to a focus on the scaling up of a techno-centric vision of agricultural transformation. To counter this, there is need for ongoing dialogue to develop a shared and more complete understanding of justice that should be central to how agricultural transformation is integrated into the UNFCCC.